Comparison of Leading English Translations of the Holy Quran by Muslims – Their Format and Distinctive Features in the Age of AI (ChatGPT) - Dr. Atiq-Ur-Rehman (Al Manhal Research Journal, 2024)
After the rendition of the Holy Quran in Western languages especially the translation of the Holy Quran by Alexander Ross and George Sale in the English Language Muslims attempted to translate the Holy Quran. However, they believed that no translation could stand for the Arabic Text of the Quran. This study evaluates their contribution and conducts a comparative analysis to explore their components and distinctive features along with the example of translations generated by ChatGPT of the selected translators, and its differences. errors or accuracy. AI (Artificial Intelligence) technology plays a transformative role in generating these translations, allowing for more specific linguistic analysis, comparative studies, and broader access to translations of the Quran by leading Muslim Scholars in translating the Quran which are familiar to Muslims as well as non-Muslim readers and researchers. This research analyzes the translators’ reliability and commitment to the original Arabic meanings, sensitivity to cultural aspects, and target audiences. It evaluates the effectiveness of formatting and explanations in enhancing comprehension for readers unfamiliar with Arabic. By analyzing the translations, on the one hand, this study reveals how each translator's scholarly background and interpretative framework influence their rendition of the Quranic text. The findings provide implications and important insights into the richness of Quranic translations, highlighting their role in advancing Islamic scholarship in the English-speaking world on the other hand, it evaluates the evolving as well as alarming challenges posed by the AI Tools, especially ChatGPT in rendition of the Quran.